The Rare Ones. Female Kinships, Discursive Mediations and Period Tensions in «Confesiones de Dorish Dam» by Delia Colmenares and «Las Memorias de Mamá Blanca» by Teresa de la Parra (Castilla. Estudios de Literatura, 2021)
Confesiones de Dorish Dam (1929) by Delia Colmenares (1887-1968) and Las memorias de Mamá Blanca (1929) by Teresa de la Parra (1889-1936) are two novels that react to the new trends that emerged in the second decade of the twentieth century, explicitly in the case of the avant-gardes and implicitly in the case of regionalism. In this article, rather, I propose that both novels are close to modernist and postmodernist aesthetics. Both also fictionalize minor genres such as the diaries and memoirs to create a gender alliance that has some tensions. In addition, from a sui generis perspective and in a context of modernization, they construct alternative female characters, dissident in de la Parra and transgressor (lesbian) in Colmenares.
Keywords: mediations; modernism; postmodernism; avant-garde; regionalism; Colmenares; de la Parra